2017
DOI: 10.3389/fpsyg.2017.00476
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar tDCS Does Not Enhance Performance in an Implicit Categorization Learning Task

Abstract: Background: Transcranial Direct Current Stimulation (tDCS) is a form of non-invasive electrical stimulation that changes neuronal excitability in a polarity and site-specific manner. In cognitive tasks related to prefrontal and cerebellar learning, cortical tDCS arguably facilitates learning, but the few studies investigating cerebellar tDCS, however, are inconsistent.Objective: We investigate the effect of cerebellar tDCS on performance of an implicit categorization learning task.Methods: Forty participants p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Table 1 shows an overview of the main characteristics of the selected studies. Of these 32 studies, 15 studies applied both anodal and cathodal stimulation (ID: 4, 10, 14, 19, 21, 22, 24, 27, 28, 29, 31, and 32) [ 17 , 23 , 27 , 30 , 32 , 34 36 , 39 – 41 , 43 , 44 ], 14 anodal (ID 1, 5, 6, 7, 8, 11, 12, 13, 15, 16, 18, 20, 23, and 30) [ 14 , 18 21 , 24 26 , 29 , 31 , 33 , 42 , 45 ], and three cathodal tDCS (ID: 3, 9, and 26) [ 16 , 22 , 38 ] (Table 1 ). In study 2 [ 15 ] were reported three experiments, each one comparing anodal and cathodal stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows an overview of the main characteristics of the selected studies. Of these 32 studies, 15 studies applied both anodal and cathodal stimulation (ID: 4, 10, 14, 19, 21, 22, 24, 27, 28, 29, 31, and 32) [ 17 , 23 , 27 , 30 , 32 , 34 36 , 39 – 41 , 43 , 44 ], 14 anodal (ID 1, 5, 6, 7, 8, 11, 12, 13, 15, 16, 18, 20, 23, and 30) [ 14 , 18 21 , 24 26 , 29 , 31 , 33 , 42 , 45 ], and three cathodal tDCS (ID: 3, 9, and 26) [ 16 , 22 , 38 ] (Table 1 ). In study 2 [ 15 ] were reported three experiments, each one comparing anodal and cathodal stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Several preliminary studies have reported positive effects of anodal ctDCS on verbal fluency [286] and pain perception [287] in healthy subjects and cognitive symptoms in Parkinson’s patients [217]. While other studies have observed no effect on cognitive learning [288] or memory [289], for example. A meta-analysis of cognition studies found cognitive processes were influenced by anodal ctDCS but to a lesser extent than motor-related effects [290].…”
Section: Non-invasive Stimulation In Humansmentioning
confidence: 99%
“…Indeed, tES has been found to have beneficial effects when applied to a number of different brain areas, including specific regions of the cerebral and cerebellar cortices [6,7]. Although such positive reports highlight the potential of tES, other studies have shown no results or negative ones [8,9]. The causes of this variability need to be understood in order for tES to reach its potential.…”
Section: Introductionmentioning
confidence: 99%